TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

Microwave-assisted synthesis: Crystallinity-driven donor-acceptor covalent organic frameworks for high-performance room-temperature HCl vapor sensing - Chang Liu; Junxi Cheng; Zihan Qin; Baole Wang; Zhengyang Cheng; Miaomiao Liu; Yichen Gong; Ning Tian; Qihua Sun; Hua Zhuo; Zhaofeng Wu (Chemical Engineering Journal, 2026)

Applications of AI-assisted interpreter Raman spectroscopy platform for rapid and accurate cefotaxime-resistant Escherichia coli classification - Chenming Lu; Weifeng Zhang; Zhenfeng Zhao; Yichen Wang; Yuxuan Hu; Xiaolong Zhao; Zhanfang Zhao; Yirui Huang; Bo Zheng; Jingna Sun; Weili Hong; Pu Wang; et al. (Analytica Chimica Acta, 2026)

6PPD and 6PPD-Q driven phytotoxicity in Eichhornia crassipes: From molecular damages to ecological potential implications - Yichen Ge; Weitao Liu; Xiang Li; Jinzheng Liu; Ruiying Shi; Xinwei Shi; Aurang Zeb; Qi Wang; Jianling Wang; Cuihong Chen; Yuebing Sun (Journal of Environmental Sciences, 2026)

Threshold responses of runoff-sediment dynamics to hydrological connectivity - Taoxi Li; Qian Zeng; Yichen Yin; Gang Sun; Ruyi Zheng; Yichun Ma; Jiale Ye; Peiyao Xiao; Yaojun Liu (Journal of Hydrology, 2026)

Ternary ZnO@ZIF@COF core-shell-shell heterostructures: Energy-band cascade and layered signal amplification for biogenic amine detection - Junxi Cheng; Ting Li; Chang Liu; Yichen Gong; Xuanjun Wang; Miaomiao Liu; Yueguang Li; Hewei Yang; Zihan Qin; Zhengyang Cheng; Liyuan Cai; Qihua Sun; et al. (Chemical Engineering Journal, 2026)

From structural features to mouse acute intraperitoneal toxicity prediction: a triple computational toxicology approach for safety assessment of flavonoids - Yichen Yang; Na Zhang; Ting Ren; Lijiao Zhao; Rugang Zhong; Ning Lin; Guohui Sun (Molecular Diversity, 2026)

3D Patellar Shape is Associated with Patellar Dislocation: an Automated Coordinate Algorithm and Statistical Shape Modeling Analysis - Yichen Yan; Jie Yao; Zifan Liu; Qinqin Yang; Bin Sun; Xinguang Liu; Bin Yang; Yubo Fan (Annals of Biomedical Engineering, 2026)

Whole-Genome Resequencing Reveals Selection Signals Associated with Vibrio parahaemolyticus Stress Tolerance in Portunus trituberculatus - Dongfang Sun; Hangfeng Pan; Yichen Su; Jiayi Pan; Xianfa Zhou; Baoquan Gao; Jianjian Lv (Marine Biotechnology, 2026)

Scholar-institutional entrepreneurs in rural tourism path innovation: the case of Azheke plan in China - Kaixuan Huang; Yichen Sun; Yi Liu (Journal of Rural Studies, 2026)

One‐Pot RAA ‐ CRISPR /Cas12a Assay for Rapid Detection of Infectious Hypodermal and Haematopoietic Necrosis Virus ( IHHNV ) in Shrimp Aquaculture - Zewei Hou; Yichen Zhao; Zheng Sun; Ying Zhan; Xilin Dai; Hao Wang (Journal of Fish Diseases, 2026)
The infectious hypodermal and haematopoietic necrosis virus (IHHNV) represents a significant viral threat to global shrimp aquaculture, leading to considerable economic losses. In this study, we have developed a one‐step, one‐pot isothermal assay for the detection of IHHNV, employing recombinase‐aided amplification in conjunction with clustered regularly interspaced short palindromic repeats‐Cas12a (RAA‐CRISPR/Cas12a). The assay is performed at a constant temperature of 37°C, achieving a detection limit of 10 copies per reaction for the fluorescence assay and 1 copy per reaction for the lateral flow dipstick (LFD) assay within a 60‐min timeframe. Additionally, we evaluated the assay against four other prevalent shrimp pathogens (WSSV, DIV1, EHP, VpAHPND) and observed no cross‐reactivity. This straightforward detection method exhibits high sensitivity and specificity for IHHNV, offering a promising approach for early and rapid field diagnosis.

Cost-Effective new energy management strategies for hybrid energy storage solutions - Shuhan Wei; Yichen Sun; Chengzhi Yu; Shon Ming (Energy and Buildings, 2026)

NUFIP1-engineered exosomes modulate propofol-induced neurotoxicity in neonatal rats via the ERS apoptotic pathway - Pengyue Zhao; Yang Yan; Bin Lan; Xingpeng Yang; Yizhao Ma; Yichen Bao; Lin Qi; Xiaohui Du; Songyan Li; Wen Sun (Apoptosis, 2026)

Rap1b is a critical regulator of germinal vesicle breakdown in porcine oocytes - Mingyue Sui; Zhihao Wang; Jianqiang Sun; Ruohan Mei; Mingju Sun; Yichen Liu; Xiang Gao; Youwei Li; Yanjun Huan (Theriogenology, 2026)

Emission reduction optimization of recycling pathways for retired photovoltaic modules in China: A coupled model of life cycle assessment and evolutionary game theory - Xu Zhu; Yichen Li; Yue Zhang; Yuanyuan Sun; Wen Xu; Lu Bai (Journal of Cleaner Production, 2026)

Information content analysis of venus clouds and haze based on polarization bands of the SPICAV IR and Venspec-H instruments - Yiqi Li; Xiaobing Sun; Xiao Liu; Honglian Huang; Xiaobing Zheng; Yichen Wei; Yizhe Fan; Shun Yao (Icarus, 2026)

Century-long socioeconomic-air pollution transitions revealed by lake sediments in Northeast China - Yalan Tang; Yongming Han; Yichen Wang; Dongna Yan; Shaolong Sun; Qiyuan Wang; Dewen Lei; Hao Peng; Peng Yao; Zeyu Liu; Ulrike Dusek (Global and Planetary Change, 2026)

Cotton shell biomass–derived carbon–supported Fe2O3/Fe3O4 nanohybrids for efficient oxygen evolution reaction - Jikui Zhu; Mengting Sun; Yichen Ren; Jiangpeng Yao; Jiming Cao; Jingjing Zhang (Fuel, 2026)

Evolving Collective Intelligence for Unmanned Marine Vehicle Swarms: A Federated Meta-Learning Framework for Cross-Fleet Planning and Control - Yuhan Ye; Hongjun Tian; Yijie Yin; Yuhan Zhou; Yang Xiong; Zi Wang; Yaojiang Liu; Zinan Nie; Zitong Zhang; Yichen Wang; Jingyu Sun (Journal of Marine Science and Engineering, 2025)
The development of robust autonomous maritime systems is fundamentally constrained by the “data silo” problem, where valuable operational data from disparate fleets remain isolated due to privacy concerns, severely limiting the scalability of general-purpose navigation intelligence. To address this barrier, we propose a novel Federated Meta-Transfer Learning (FMTL) framework that enables collaborative evolution of unmanned surface vehicle (USV) swarms while preserving data privacy. Our hierarchical approach orchestrates three synergistic stages: (1) transfer learning pre-trains a universal “Sea-Sense” foundation model on large-scale maritime data to establish fundamental navigation priors; (2) federated learning enables decentralized fleets to collaboratively refine this model through encrypted gradient aggregation, forming a distributed cognitive network; (3) meta-learning allows for rapid personalization to individual vessel dynamics with minimal adaptation trials. Comprehensive simulations across heterogeneous fleet distributions demonstrate that our federated model achieves a 95.4% average success rate across diverse maritime scenarios, significantly outperforming isolated specialist models (63.9–73.1%), while enabling zero-shot performance of 78.5% and few-shot adaptation within 8–12 episodes on unseen tasks. This work establishes a scalable, privacy-preserving paradigm for collective maritime intelligence through swarm-based learning.

Earthworm intestine orchestrates dual host-microbiome detoxification of 6PPD-quinone - Ruiying Shi; Weitao Liu; Xinwei Shi; Xiang Li; Yichen Ge; Jinzheng Liu; Aurang Zeb; Yuexing Zhao; Yuebing Sun; Jing An (Journal of Hazardous Materials, 2025)

6PPD-Q driven rare and abundant taxa functional partitioning shapes soil ecological response - Xinwei Shi; Weitao Liu; Ruiying Shi; Yichen Ge; Xiang Li; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Dasong Lin; Yuebing Sun (Journal of Hazardous Materials, 2025)

Foliar exposure to 6PPD-Q disturbs photosynthetic processes and induces oxidative stress in Eichhornia crassipes - Yichen Ge; Ruiying Shi; Weitao Liu; Xiang Li; Xinwei Shi; Aurang Zeb; Yuexing Zhao; Jing An; Yuebing Sun (Journal of Environmental Management, 2025)

Nanoconfined enzymatic cascade strategy for highly efficient synthesis of D-allulose - Kan Zhan; Anni Bao; Suhai Zhang; Liang Chen; Yichen Wan; Keke Hou; Jian Hao; Lin Chaoping; Zhiyong Sun; Renchao Zheng; Yuguo Zheng (Chemical Engineering Journal, 2025)

Protic solvent-boosted lignin demethylation in protic ionic liquids - Yichen Liu; Wanting Zhao; Yuting Shi; Jian Sun (Chemical Engineering Journal, 2025)

Cellular optical imaging techniques: a dynamic advancing frontier - Yaning Li; Chuankang Li; Caiwei Zhou; Jie Wang; Weixing Li; Tianying Pan; Chenying He; Xiaodong Guan; Yichen Wang; Yingda Huang; Xianao Zhao; Lusheng Gu; et al. (Science China Life Sciences, 2025)

Differential response of runoff-sediment hysteresis relationships to watersheds hydrological structural connectivity - Taoxi Li; Ming Lei; Gang Sun; Qian Zeng; Yu Long; Yichun Ma; Yichen Yin; Peiyao Xiao; Jiale Ye; Zhongwu Li; Yaojun Liu (Journal of Hydrology, 2025)

Walnut xylem-derived activated carbon with microtubule bundle architectures for highly efficient and rapid treatment of methylene blue - Shuang Jia; Zhijie Mao; Bo Zhang; Yaru Wang; Tianyang Sun; Guanhua Jin; Chuang Wang; Yichen Lv; Shouzhu Li; Dan Sun (Journal of Environmental Chemical Engineering, 2025)

Synthesis, characterization, and in vitro hypolipidemic mechanisms of sugar-SA triazole conjugates as potent pancreatic lipase inhibitors - Ruge Cao; Jingxin Li; Yue Sun; Yichen Li; Xiao-Lin Zhang; Han Ding; Xue-Wei Liu (Food Chemistry, 2025)

Tribopotential mediated ferroelectric polarization for versatile reconfigurable p–n junction - Keteng Zhang; Jinran Yu; Yichen Wei; Liuqi Cheng; Zhenyu Feng; Jie Gong; Zhong Lin Wang; Qijun Sun (Chemical Engineering Journal, 2025)

Microwave-assisted one-pot synthesis of hierarchical MnCO3/NiO heterojunction with superior energy storage performance for aqueous supercapacitor - Yin Sun; Gaoyong Zhang; Shuhuang Tan; Haowei Wang; Yichen Liu; Chengqi Sun; Banglin Deng; Kun Zhang; Zhaoqing Gao; Naibao Huang (Chemical Engineering Journal, 2025)

Multi-omics analysis reveals an endogenous competitive regulatory mechanism for resistance to Vibrio parahaemolyticus in the swimming crab, Portunus trituberculatus - Dongfang Sun; Xianfa Zhou; Yichen Su; Baoquan Gao; Ping Liu; Jianjian Lv (Fish & Shellfish Immunology, 2025)

Quinoa greens as a novel plant food: a review of its nutritional composition, functional activities, and food applications - Huange Huang; Qiang Wang; Jianxin Tan; Chunxiang Zeng; Junying Wang; Jingwei Huang; Yichen Hu; Qi Wu; Xiaoyong Wu; Changying Liu; Xueling Ye; Yu Fan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Tetrahedral framework nucleic acid-based delivery of microRNA-29b: A precision nanotherapeutic strategy for oral submucous fibrosis - Xiao Fu; Mei Zhang; Chenpeng Chen; Xin Qin; Qianqian He; Yichen Yang; Siqi Xu; Guanjun Chen; Haiyu Xian; Guanyu Sun; Yao He; Yunfeng Lin; et al. (Chemical Engineering Journal, 2025)

Short-Term Postoperative Mechanical Properties of Graft in Anterior Cruciate Ligament Reconstruction - Zizhan Lian; Bin Sun; Xiangfei Kong; Yichen Yan; Jie Yao; Bin Yang; Yubo Fan (Journal of Medical and Biological Engineering, 2025)

Pedigree reconstruction based on target sequencing in Pacific white shrimp Litopenaeus vannamei - Junqing Yang; Yang Yu; Yizhou Zhou; Zhenning Bao; Yichen Liu; Jinsheng Sun; Fuhua Li (Aquaculture, 2025)

Characterising vibration patterns of winter jujube trees to optimise automated fruit harvesting - Zhouzhou Zheng; Yaohua Hu; Jianxin Dong; Pengfei Zhao; Yixue Liu; Xintong Jiang; Yichen Qiao; Shangpeng Sun; Yuxiang Huang (Biosystems Engineering, 2024)

Spaceborne high-spectral-resolution lidar ACDL/DQ-1 measurements of the particulate backscatter coefficient in the global ocean - Yichen Yang; Yudi Zhou; Iwona S. Stachlewska; Yongxiang Hu; Xiaomei Lu; Weibiao Chen; Jiqiao Liu; Wenbo Sun; Suhui Yang; Yuting Tao; Lei Lin; Weige Lv; et al. (Remote Sensing of Environment, 2024)

Recent advances on transport and transformation mechanism of nanoplastics in lung cells - Simeng Zhang; Hangxi Zhang; Yichen Li; Zhiwei Sun; Yueyue Chen (Science of The Total Environment, 2024)

Key aroma compounds associated with umami perception of MSG in fried Takifugu obscurus liver - Yuqian Zheng; Yichen Sun; Yiwen Zhu; Wenli Wang; Imre Blank; Shi Liu; Yin Zhang; Ye Liu; Yuan Liu (Food Research International, 2024)

A kinetic study of nonthermal plasma pyrolysis of methane: Insights into hydrogen and carbon material production - Xuchu Yuan; Jintao Sun; Yichen Ma; Yaolin Wang; Bowen Liu; Yuxiang Cai; Xue Yong; Xin Tu (Chemical Engineering Journal, 2024)

Topological surface states in quasi-two-dimensional magnetic kagome metal EuTi3Bi4 - Zhicheng Jiang; Tongrui Li; Jian Yuan; Zhengtai Liu; Zhipeng Cao; Soohyun Cho; Mingfang Shu; Yichen Yang; Zhikai Li; Jiayu Liu; Jianyang Ding; Zhonghao Liu; et al. (Science Bulletin, 2024)

Identification of aurones and chalcones as the main contributors to xanthine oxidase inhibitory activity of snow chrysanthemum - Han Xiao; Hui Wang; Shiwei Sun; Jiaying Ma; Hao Wang; Yichen Yin; Wei Wang (Food Bioscience, 2024)

Effect of ammonia/hydrogen blending and injection modes on combustion emission and performance of marine engine - Xiuxiu Sun; YiChen Jiang; Peixin Zhao; Guoxi Jing; Teng Ma (Fuel, 2024)

Association of exposure to ultraviolet radiation and warm-season ozone air pollution with incident age-related macular degeneration: A nationwide cohort study in China - Yanlin Qu; Yichen Jiang; Guanran Zhang; Huihuan Luo; Weiting Hu; Zhenyu Wu; Xia Meng; Renjie Chen; Huixun Jia; Xiaodong Sun (Science of The Total Environment, 2024)

Robust and tunable hydrogels strengthened by dynamic amphiphilic ionic domains - Wenzhe Xiao; Ting He; Wanting Zhao; Wenjin Li; Yichen Liu; Cheng Li; Qizhen Luo; Weidong Zhao; Jipeng Yan; Jian Sun (Chemical Engineering Journal, 2024)

Towards multi-views cloud retrieval accounting for the 3-D structure collected by directional polarization camera - Haixiao Yu; Xiaobing Sun; Bihai Tu; Rufang Ti; Jinji Ma; Jin Hong; Cheng Chen; Xiao Liu; Honglian Huang; Zeling Wang; Safura Ahmad; Yi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Bone tissue engineering based on sustained release of MiR29c-modified framework nucleic acids from an injectable hydrogel - Jiafei Sun; Yang Gao; Yangxue Yao; Yong Li; Maogeng Feng; Long Bai; Xingyu Chen; Yichen Ge; Yunfeng Lin; Xiaoxiao Cai (Chemical Engineering Journal, 2024)

miR-377-3p Regulates Hippocampal Neurogenesis via the Zfp462-Pbx1 Pathway and Mediates Anxiety-Like Behaviors in Prenatal Hypoxic Offspring - Bin Wang; Yichen Zhu; Bin Wei; Hongtao Zeng; Pengjie Zhang; Lingjun Li; Hongyan Wang; Xiaohui Wu; Yufang Zheng; Miao Sun (Molecular Neurobiology, 2024)

Drift and afterburning effect on rocket exhaust plume impingement and optimization of deflector - Chengeng Zhao; Yifei Su; Zhongyi Sun; Yichen Wang; Guigao Le (Advances in Space Research, 2024)

Study on Mooring Design of 15 MW Floating Wind Turbines in South China Sea - Mingsheng Chen; Jiale Jiang; Wei Zhang; Chun Bao Li; Hao Zhou; Yichen Jiang; Xinghan Sun (Journal of Marine Science and Engineering, 2023)
Wind turbines and floating platform upsizing are major trends in the current offshore wind development. However, harsh environmental conditions increase the risk of anchor dragging and mooring failure when deploying large offshore floating wind turbines. Therefore, it is necessary to design a mooring system for the specific deployment site. This study aims to perform the mooring system design of a floating offshore wind turbine (FOWT) operated in the South China Sea, which is a combination of the IEA 15 MW wind turbine and UMaine VolturnUS-S floating platform. Hydrodynamic coefficients were calculated based on the potential flow theory, considering the environmental loads in the South China Sea. Additionally, the hydrodynamic coefficients were imported into AQWA to calculate the time-domain mooring tension. The mooring design parameters, such as mooring line length, nominal sizes, and anchor point, were determined using the criterion of anchor uplift, maximum breaking strength, and fatigue life, respectively. The design criterion required that the anchor uplift is not more than the allowable value, the long-term breaking limit of mooring with a 100-year return period should be less than the maximum breaking limit, and the fatigue damage accumulation in 50 years should be safe. The mooring design procedure provides a reference for mooring system design and safe operation of large floating wind turbines in the South China Sea.

Electroacupuncture Inhibits Pain Memory and Related Anxiety-Like Behaviors by Blockading the GABAB Receptor Function in the Midcingulate Cortex - Xiaoyu Li; Yichen Zhu; Haiju Sun; Zui Shen; Jing Sun; Siqi Xiao; Xiaofen He; Boyu Liu; Yifang Wang; Yuxin Hu; Boyi Liu; Yi Liang; et al. (Molecular Neurobiology, 2023)
Pain memory is commonly considered an underlying cause of chronic pain and is also responsible for a range of anxiety. Electroacupuncture (EA) has been shown to ameliorate pain memories and exert anti-anxiety effects. Previous research has indicated that GABAergic neurons and/or GABA receptors (GABARs) in the midcingulate cortex (MCC) have potential associations with chronic pain and anxiety. However, there is no known empirical research that has specifically studied the effects of EA on the GABAergic system in the MCC. Here, we used cross-injection of carrageenan to establish the pain memory rats model. Immunofluorescence were used to detect the excitability of GABAergic neurons within MCC. Von Frey filament, elevated zero maze, and open field tests were used to measure mechanical allodynia and anxiety-like behaviors, combined with chemogenetic and pharmacologic technologies. Finally, this study provides evidence that pain memories contribute to generalized negative emotions and that downregulating the activity of GABAergic neurons within MCC could block pain memories and reverse anxiety emotion. Specifically, GABA B R is involved in pain memory and related anxiety-like behaviors. Activation of GABAergic neurons in the MCC did not reverse the effects of EA on pain memories and related anxiety-like behaviors, whereas these effects could be reversed by a GABA B R agonist. These findings highlight the functional significance of GABA B R in the EA-mediated attenuation of pain memories and related anxiety-like behaviors in rats.

Parenting Practices Are Associated With Adolescent Food Choices During Independent Eating Occasions - Marla Reicks; Karina R. Lora; Yichen Jin; Alex K. Anderson; Lillie Monroe-Lord; Blake L. Jones; Glade L. Topham; Jinan Banna; Carolyn Gunther; Laura C. Hopkins; Rickelle Richards; Siew Sun Wong (Journal of the Academy of Nutrition and Dietetics, 2023)

Heterogeneous activation of permonosulfate by biochar supporting CuCoFe layered double hydroxide for rapid degradation of phenanthrene - Lin Wu; Tao Jin; Dan Li; Liping Wang; Yichen Sun (Journal of Environmental Chemical Engineering, 2023)

Effects of outrigger configuration on trimaran stability in longitudinal waves - Yichen Jiang; Mingzhe Wang; Junyu Bai; Yuan Sun; Jiawen Li (Ocean Engineering, 2023)

Structural characteristics and genetic mechanism of transfer zones in an extensional rift zone: An example from the Xihu Sag, East China Sea Basin - Yanjun Cheng; Zhiping Wu; Bin Xu; Jie Zhang; Yichen Chu; Yining Dai; Lili Xu; Wenjie Sun; Saiting Ma (Tectonophysics, 2023)

Evaluation of a novel carbon-based micro-nano zero-valent iron composite for immobilization of heavy metals in soil - Song Guo; Huifen Yang; Qiwei Sun; Ge Zhang; Tong Zhao; Yichen Zhou; Xuan Li; Pu Gao (Journal of Environmental Chemical Engineering, 2023)

Ar-turmerone suppresses Aspergillus flavus growth and aflatoxin accumulation: Finding a new antifungal agent based on stored maize - Zheyu Li; Yanan Sun; Linghui Gu; Yuchi Wang; Mingqin Xu; Yunhao Zhou; Yichen Hu; Wenbo Ma (Food Research International, 2023)

Identification and evaluation of potential probiotics against skin-ulceration disease in the Chinese tongue sole (Cynoglossus semilaevis) - Zhihan Zuo; Bijiao Shang; Hongrui Liu; Jiacheng Sun; Wenyue Li; Yichen Liu; Jinsheng Sun (Fish & Shellfish Immunology, 2023)

The electrical activity of a thunderstorm under high dust circumstances over Beijing metropolis region - Chunfa Sun; Dongxia Liu; Xian Xiao; Yichen Chen; Zirui Liu; Yang Sun (Atmospheric Research, 2023)

Microplastic pollution destabilized the osmoregulatory metabolism but did not affect intestinal microbial biodiversity of earthworms in soil - Ronggui Tang; Minshen Ying; Yongming Luo; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Tao Sun; Yutao Cao; Zhihan Diao; Yuxin Zhang; Yichen Lian; Keyi Chen; Yan Yan; et al. (Environmental Pollution, 2023)

Economical amidoxime-functionalized non-porous β-cyclodextrin polymer for selective detection and extraction of uranium - Yichen Sun; Ran Leng; Xinjie Ma; Jiangping Zhang; Bing Han; Guixia Zhao; Yuejie Ai; Baowei Hu; Zhuoyu Ji; Xiangke Wang (Chemical Engineering Journal, 2023)

The Mesozoic tectonic evolution of the East China Sea Basin: New insights from 3D seismic reflection data - Yanjun Cheng; Zhiping Wu; Bin Xu; Yining Dai; Yichen Chu; Jie Zhang; Mingming Chen; Saiting Ma; Wenjie Sun; Lili Xu (Tectonophysics, 2023)

Hippo Signaling Regulates Blastema Formation During Limb Regeneration in Chinese Mitten Crab (Eriocheir sinensis) - Yiran Wang; Xinrui Huang; Qiao Zhou; Yuxin Tian; Jinmei Zuo; Zengzhi Yuan; Yichen Liu; Ju Li; Jinsheng Sun (Marine Biotechnology, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

Optimization of medical waste recycling network considering disposal capacity bottlenecks under a novel coronavirus pneumonia outbreak - Xueyun Mei; Hao Hao; Yichen Sun; Xinyang Wang; Yanjun Zhou (Environmental Science and Pollution Research, 2022)

Establishment of pediatric developmental dysplasia of the hip biobank: Shanghai children’s hospital experience - Dan Yang; Shiqi Wang; Chenghui Ke; Qichao Ma; Lingyan Fan; Yichen Wang; Mengjie Chen; Hao Ying; Sun Wang; Qin Jiao; Yang Shen; Lihua Zhao (Cell and Tissue Banking, 2022)
Developmental dysplasia of the hip (DDH) is a debilitating condition that affects 1–7% of newborns. Children with DDH, not treated early and effectively, will easily lead to disability. A better understanding of the biology of DDH is critical to the development of prognostic biomarkers and novel therapies. The purpose of this study was to establish a biobank of DDH genetic resources, to facilitate clinical and basic scientific research. The biological specimen and clinical data of DDH were collected in Shanghai Children’s Hospital from 2014 to 2021. The collection of blood samples was performed at definitive diagnosis and review, tissue specimens were performed at definitive surgery. The clinical data was collected at the whole stage of DDH patients at diagnosis, treatment and follow-up. A total of 528 patients with DDH were enrolled in this study, 90 were men and 438 were women, with the mean age of 4.67 years. The numbers of tissue and blood specimens reached 2172 and 1490, respectively. The quality test results showed that the DNA concentration decreased slightly with the extension of storage time, but the DNA purity did not change. Meanwhile, the extension of storage time slightly affected the stability of protein of tissue samples but did not affect the expression of the housekeeping gene. The DDH biobank built has the potential of monitoring disease pathogenesis and progress, which could provide specimens to the researchers improving the biological understanding and provide guidance of clinical treatment of this disease to clinicians.

Spatial-temporal distributions and influential factors of phthalate acid esters in sediments of three lakes in Inner Mongolia - Yan Ma; Tong Liu; Bo-Tao Zhang; Yan Liu; Peng Shao; Chen Sun; Yichen Zhang; Jiale Bi; Yunkai Dong; Shengrui Wang; Guoming Zhang (Environmental Science and Pollution Research, 2022)

Characteristics of Slamming Pressure and Force for Trimaran Hull - Zhe Sun; Xupeng Sui; Yanzeng Deng; Li Zou; A. Korobkin; Lixin Xu; Yichen Jiang (Journal of Marine Science and Engineering, 2021)
In this paper, the characteristics of the impact pressure and force of a trimaran section was studied by Computational Fluid Dynamics (CFD). The time domain features of the slamming pressure or force showed a strong correlation with the penetration depth regardless of the specific ways of water entry. The effects of velocity and acceleration on the impact pressure and force were analyzed. It was found that the initial impact of the main hull and the wet-deck slamming were predominantly affected by the entry velocities, whilst the acceleration had almost no effect for initial impact. The impact velocity presented a quadratic relation with slamming pressure/forces, and the relation between acceleration and wet-deck slamming pressure/force was linear. These were consistent with the patterns implied by analytical models such as the Wagner or MLM (Modified Logvinovich model) theories.

Long-term fencing decreases plant diversity and soil organic carbon concentration of the Zoige alpine meadows on the eastern Tibetan plateau - Xinwei Wu; Yichen Wang; Shucun Sun (Plant and Soil, 2021)

Study on the Influence of Temperature on the Temporal and Spatial Distribution Characteristics of Natural Cavitating Flow around a Vehicle - Tiezhi Sun; Jianyu Zhang; Xiaoshi Zhang; Yichen Jiang (Journal of Marine Science and Engineering, 2020)
Cavitation involves complex multiphase turbulence and has important research significance. In this study, the Schnerr–Sauer cavitation model was used to model cavitation, and the detached-eddy simulation (DES) method was used to calculate the unsteady natural cavitating flow. The predicted results are in good agreement with experimentally measured cavity evolution and pressure values, demonstrating the effectiveness of this numerical method. Low temperature causes changes in the properties of water. The density of water at 0° is 999.84 kg/m3 and the density of water at 25° is 997.04. Cavitation evolution and shedding are analyzed at temperatures of 0 °C and 25 °C. The results showed that lower temperature increased the frequency of cavitation and enhanced pressure pulsation. At the same time, low temperature also increases the frequency of cavity shedding and shortens the cycle. In addition, based on the Ω method, the difference between vortex dynamics at various temperatures was studied, and it was found that different cavity stages showed different vortex structure characteristics, and lower temperature would aggravate the change of wake vortex structure. At the same time, the analysis of the turbulence characteristics in the downstream of the cavity shows that the lower temperature reduces the velocity pulsation and reduces the turbulence integral scale. At the end of the model, large-scale pulsations are transformed into small-scale pulsations.

Investigating Lightning Characteristics through a Supercell Storm by Comprehensive Coordinated Observations over North China - Dongxia Liu; Xiushu Qie; Yichen Chen; Zhuling Sun; Shanfeng Yuan (Advances in Atmospheric Sciences, 2020)

Wind Tunnel Test on the Effect of Solidity on Near Wake Instability of Vertical-Axis Wind Turbine - Li Zou; Kun Wang; Yichen Jiang; Aimin Wang; Tiezhi Sun (Journal of Marine Science and Engineering, 2020)
Owing to the rapid development of the offshore wind power technology and increasing capacity of wind turbines, vertical-axis wind turbines (VAWTs) have experienced a great development. Nevertheless, the VAWT wake effect, which affects the power generation efficiency and rotor fatigue life, has not been thoroughly understood. In this study, the mid-span wake measurements on a VAWT in six different configurations were conducted. This study aimed to investigate the effect of solidity on near wake instability of vertical-axis wind turbine. By using the wavelet analysis method to analyse the measured velocity (or pressure) time series signals on a multi-scale and with multi-resolution, the dynamic characteristics of the coherent vortex structures in the wake evolution process were determined. The results show that with increasing solidity, the VAWT wake develops into a bluff body wake mode. In addition, a characteristic frequency that is lower than the low-frequency large-scale vortex shedding frequency occur. The wavelet transform was used to decompose and reconstruct the measured data, and the relationship between the low-frequency large-scale vortex shedding and lower frequency pulsation was established. The results provide important data for numerical modelling and new insights into the physical mechanism of the VAWT wake evolution into a bluff body wake.

Investigation of Blade Tip Shape for Improving VAWT Performance - Yichen Jiang; Chenlu He; Peidong Zhao; Tiezhi Sun (Journal of Marine Science and Engineering, 2020)
Vertical axis wind turbine (VAWT) is a competitive power generation device due to structural simplicity, wind direction independence, no yaw mechanism required, easier maintenance, and lower noise emission. However, blade tip vortex will be generated at both ends of the blade during the rotation, resulting in torque loss and efficiency reduction. In this paper, computational fluid dynamics is used to study blade tip vortex and its reduction technique of a single-blade VAWT rotor in real scale. By monitoring the force and flow field at different heights of the blade, the influence ranges of tip vortex are obtained. The reduction effect of the bulkhead obtained from the blade profile curve is studied, and the size of the bulkhead is optimized. On the basis of adding the optimal bulkhead, the influence of the supporting strut is also explored. The joint action is obtained by changing the location of the supporting strut. The results show that the top supporting strut-bulkhead structure is the optimal position. The power-extraction efficiency of the rotor with this integrated structure is significantly improved at optimal tip speed ratios (TSRs) and higher TSRs.

Levo-tetrahydropalmatine Attenuates Neuron Apoptosis Induced by Cerebral Ischemia–Reperfusion Injury: Involvement of c-Abl Activation - Ruoxi Sun; Yichen Song; Shanshan Li; Zhanqiang Ma; Xueyang Deng; Qiang Fu; Rong Qu; Shiping Ma (Journal of Molecular Neuroscience, 2018)